2015
DOI: 10.2147/idr.s67275
|View full text |Cite
|
Sign up to set email alerts
|

Impact of space flight on bacterial virulence and antibiotic susceptibility

Abstract: Manned space flight induces a reduction in immune competence among crew and is likely to cause deleterious changes to the composition of the gastrointestinal, nasal, and respiratory bacterial flora, leading to an increased risk of infection. The space flight environment may also affect the susceptibility of microorganisms within the spacecraft to antibiotics, key components of flown medical kits, and may modify the virulence characteristics of bacteria and other microorganisms that contaminate the fabric of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
140
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(141 citation statements)
references
References 81 publications
1
140
0
Order By: Relevance
“…For instance, some microbial isolates were collected from astronauts and filter debris during orbital spaceflights on the International Space Station (ISS) (Checinska et al, 2015;Venkateswaran et al, 2014). It has been reported that the space environment can alter the microbial growth rate, virulence, and antibiotic susceptibility (Kim et al, 2013;Klaus & Howard, 2006;Mora et al, 2016;Rosenzweig, Ahmed, Eunson, & Chopra, 2014;Taylor, 2015;Urbaniak et al, 2018;Wilson et al, 2007). In addition, many studies have shown that the extreme environment of space plays an important role in dysregulation of the human immune system (Crucian et al, 2018;Kaur, Simons, Castro, Ott, & Pierson, 2005;Taylor, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, some microbial isolates were collected from astronauts and filter debris during orbital spaceflights on the International Space Station (ISS) (Checinska et al, 2015;Venkateswaran et al, 2014). It has been reported that the space environment can alter the microbial growth rate, virulence, and antibiotic susceptibility (Kim et al, 2013;Klaus & Howard, 2006;Mora et al, 2016;Rosenzweig, Ahmed, Eunson, & Chopra, 2014;Taylor, 2015;Urbaniak et al, 2018;Wilson et al, 2007). In addition, many studies have shown that the extreme environment of space plays an important role in dysregulation of the human immune system (Crucian et al, 2018;Kaur, Simons, Castro, Ott, & Pierson, 2005;Taylor, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the space environment can alter the microbial growth rate, virulence, and antibiotic susceptibility (Kim et al, 2013;Klaus & Howard, 2006;Mora et al, 2016;Rosenzweig, Ahmed, Eunson, & Chopra, 2014;Taylor, 2015;Urbaniak et al, 2018;Wilson et al, 2007). In addition, many studies have shown that the extreme environment of space plays an important role in dysregulation of the human immune system (Crucian et al, 2018;Kaur, Simons, Castro, Ott, & Pierson, 2005;Taylor, 2015). Animal experiments also indicated that splenic lymphocyte, monocyte/macrophage, and granulocyte counts were significantly reduced in mice during spaceflight compared with ground control mice (Baqai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Several spaceflight experiments have assessed the effects of microgravity on the growth of a variety of bacteria in liquid culture, but no consistent picture has emerged. Depending on the species, strain, hardware, and growth conditions, reports range from spaceflight promoting increased, decreased, or no growth differences between FL and GC samples (reviewed in [4,6,[25][26][27]). Due to hardware limitations, most spaceflight experiments only measure the final number of cells in cultures after samples have been returned to Earth.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in these fundamental physical parameters are thought to alter the rates at which gases, nutrients, signaling molecules, and waste products are exchanged between microbes and their surroundings. Numerous studies have sought to understand how microbes sense and respond to the spaceflight environment (reviewed in [4][5][6][7][8]), but to date no coherent model has been forthcoming.…”
Section: Introductionmentioning
confidence: 99%
“…The space flight environment (microgravity, cosmic radiation) has many stress factors that may induce different effects on human physiology and health, including reduction in the immune competence in astronauts, leading to an increase in the risk of infection, altered antibiotic susceptibility [74][75][76], as well as a possible development of premalignant/malignant disorders, especially during long-term space flights [77]. In cells grown in space, various changes have been observed, including cytoskeleton rearrangements, altered gene expression, and changes in cell signaling [78,79].…”
Section: Differential Effects Of Altered Gravity On Guanylyl Cyclase-mentioning
confidence: 99%